MEASURING AND ANALYSIS OF COMPETITION INTENSITY IN THE SUGAR MARKET IN SERBIA - Krstić, Bojan; Radivojević, Vladimir; Stanišić, Tanja (Economics of Agriculture, 2016)
Competition intensity is an important factor of social welfare in all market economies. The purpose of this paper is to establish a methodological framework for measuring and analyzing competition intensity in the sugar market in Serbia. There are several indicators of competition intensity that are used in market analysis. Results obtained by these indicators provide a good basis for objective, unbiased, and to some extent standardized reasoning and identifcation of anti-competitive behavior. The study is made by using descriptive statistics, comparative and correlation analysis. The results of the measurement of competition intensity in the sugar market in Serbia show signifcant problems in the process of establishing an effcient market economy in the Republic of Serbia. The paper is useful to the competition authority, providing signifcant fndings of competitive conditions in the sugar market in Serbia, but also to the researchers in the feld of market analysis, by providing them with an applicable methodological framework for measuring and analyzing competition intensity in the markets of other products in complex process industries.